Construction of the "Research-Psychology Co-Education" Model and Psychological Healing System under the Background of Global Study Tours - Dan Yao; Ran Gao; Xun Jiao (Education Research on Study Tours and Practice, 2026)
Current study tour practices for primary and secondary school students are generally superficial, characterized by "valuing sightseeing over research, knowledge over emotion, and teaching over psychology". Meanwhile, mental health education is confronted with practical dilemmas such as limited fields, insufficient experience, weak healing effects, and delayed intervention. The separate operation of the two can hardly meet the needs of cultivating sound personality of adolescents in the new era. Taking global study tours as the practical field and psychological healing as the core value, this paper proposes an innovative "Research-Psychology Co-Education" model with the core idea of "promoting education through research and nurturing emotion with heart", and systematically constructs a six-in-one study tour healing education system covering concept, goal, curriculum, implementation, mechanism and guarantee. This paper reveals the generation mechanism of the model from the three logical chains of problem orientation, value orientation and practice orientation, and clarifies the internal coupling relationship between the education mechanism and the system framework to enhance theoretical interpretation and logical coherence. Combined with regional practice cases in Qiqihar, this paper explains the formation logic, practical problem orientation, operation mechanism and implementation path of the model, integrates innovative designs such as traceless healing, double-teacher collaboration, experiential infiltration and digital evaluation, strengthens the connection between theory and practice, supplements students’ real feedback, on-site observation records and typical case details, as well as implementation effects and application scenarios. It provides a reproducible theoretical framework and practical paradigm for regionally promoting the in-depth integration of study tour practices and mental health education and improving adolescents’ psychological literacy.